Caregivers readiness to disclose HIV status : experiences and challenges of child disclosure in South Africa - Tapscott, Kimberley (Department of Public Health and Family Medicine, 2016)
Disclosure of HIV status to children is a challenging process for caregivers, as it involves discussing a highly stigmatised disease, which may cause psychological stress to a child. Despite the benefits of disclosing, rates of HIV disclosure remain low as caregivers face various obstacles preventing them from disclosing, and this can have long-lasting effects on the treatment adherence of HIV-positive children. This qualitative study explored the perspectives and experiences of caregivers, in order to understand their readiness to disclose HIV status to their children, and address the factors that assist and hinder the process. Caregivers of HIV positive children (aged 5-15 years) participated in two focus group discussions (11 in each), and in-depth interviews were conducted with eight additional caregivers. Two healthcare workers and 10 NGO staff were also interviewed. Three key themes emerged from the data: caregivers' avoidance or delay of disclosure, factors related to caregivers' motivations to disclose, and caregiver's perception of child readiness for disclosure. The findings support the view that caregiver readiness is a key element of child disclosure. The research identified how caregivers can be educated about the benefits of disclosure, and be guided to take responsibility for the process. As there is a lack of context-specific and culturally-sensitive recommendations for child disclosure in South Africa, this research can be used to broaden the case base to inform the development of standardised guidelines that will assist caregivers to effectively communicate and manage the process of HIV disclosure with their children.